The economical production of pork - Dorman, Roy Nathan (My University, 1904)
Introduction: The production of pork is one of the most important economical problems that the farmer and stock raiser has to solve. As a rule in this section of the country, we have an abundance of feed, and a fair variety and also a good stock of hogs to feed these products to, but the scientific feeder is most interested in how to utilize these products to secure the largest net profit. In other words, he wants to know what combination of feeds is the most economical. The Experiment Stations of the different states are solving many of these problems, since the farmer cannot afford to feed many of the different products until he knows they are profitable. The farmer and stock raiser then may profit by experiments carried on under scientific supervision. What feeds can we afford to make use of, with pork and feed at a given price? The supply and demand according to the cost of production. If the cost of feed is high the cost of pork must be accordingly high or the supply will diminish. In other words, the supply and demand must be kept in equilibrium in order to keep a commodity at normal value. In this connection is where the scientific feeder shows his skill over the one who does not realize the importance of economic feeding.
Citation: Dorman, Roy Nathan. The economical production of pork. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Pork; Pork Production; Agricultural Economics; Theses